Cicil emas BSI: solusi cerdas untuk pelunasan haji - Sabrina, Siti Nabila Zida (Maliki Interdisciplinary Journal, 2026)
The increase in Hajj Travel Costs (BPIH) and economic uncertainty pose significant challenges for prospective pilgrims in preparing Hajj financing. Therefore, an effective financial planning strategy based on Islamic principles is required. This study aims to analyze the effectiveness of Islamic gold investment through the Cicil Emas (CILEM) product of Bank Syariah Indonesia (BSI) in preparing Hajj financing. This research employs a descriptive qualitative approach using observation and field data analysis of customers at BSI KCP Pandaan A. Yani. The results indicate that customers utilizing the CILEM product demonstrate better financial readiness in completing BPIH payments compared to those who do not adopt Islamic gold investment strategies. Islamic gold investment has proven effective in preserving asset value and mitigating the impact of rising Hajj costs.